n-5-6=8(n-6)-8(n-6)

Simple and best practice solution for n-5-6=8(n-6)-8(n-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-5-6=8(n-6)-8(n-6) equation:



n-5-6=8(n-6)-8(n-6)
We move all terms to the left:
n-5-6-(8(n-6)-8(n-6))=0
We add all the numbers together, and all the variables
n-(8(n-6)-8(n-6))-11=0
We calculate terms in parentheses: -(8(n-6)-8(n-6)), so:
8(n-6)-8(n-6)
We multiply parentheses
8n-8n-48+48
We add all the numbers together, and all the variables

Back to the equation:
-()
We add all the numbers together, and all the variables
n=0

See similar equations:

| b/4+2b/5-5=-3 | | h−3/2=2 | | 5x+69=-3x+43 | | (m+200)÷4=51 | | 8-5/7x=-3 | | 17(75)+22x=1891 | | a^2+a^2=4R^2 | | 8=2-3b | | 6^x+2=-29 | | 1+5p-9=5p-8 | | -(2x-4)+3(x-)=2(x-1)-(x-3) | | 3x+x+2=x+2-10 | | i5+-2=11 | | 2=1.095^n | | -2(x+2)-x=-x-4(x+2) | | x+50+3x-6=180 | | 1/5x+1/2=1/2x+7/10 | | 7=6-c/3 | | 3(2x-15)=0.5(12x+18) | | 8/10x-3=3/10x+7 | | -7(2+2x)=-7(x-7) | | x+x-58=180 | | 33-19=2(x-9) | | 4n=17=42 | | 8y-3=5y+7 | | 7-3=-3y-43 | | 26-2y=4 | | 18-3y=20 | | -(8+7x)=-2(-3+3x)+6x | | X+(1/2x)+(1/2x)(3)=15 | | 24z−23z=−15+14 | | 6-x3/4=4 |

Equations solver categories